Universitas Negeri Padang Library Promotion Strategy in Attracting Visitors - Ardhana, Annisa Dwitya; Alfiyan, Vinny Putri; Bellini, Melani Putri; Marlini (MultiTech Publisher, 2024)
This study aims to discuss the promotional strategies employed by the Universitas Negeri Padang Library to attract visitors or users to the library. The research method used is library research or literature study with a qualitative approach to obtain data in the form of words or descriptions. The research findings indicate that library promotion strategies can be implemented through the following activities: (a) Print media, such as newspapers, magazines, and brochures; (b) Electronic media, including television, websites, and social media, which are currently popular among users, as well as radio; (c) Non-mass media, such as banners and billboards; (d) Event-based media, such as exhibitions, seminars, talk shows, and outreach programs.